Market Expansion Strategy for Copper Slag Exports of PT Freeport Indonesia - Fajar Tirtafadhitya; Febry Chairuddin Damien; Eileen Rosabel Renaningtyas; Juliater Simarmata (Jurnal Ilmu Multidisiplin, 2025)
This study explores the market expansion strategy for copper slag exports at PT Freeport Indonesia using a qualitative approach. A case study design is employed to examine internal and external factors influencing the expansion, supported by SWOT analysis. Data collection is conducted through in-depth interviews with key stakeholders, including export managers, marketing teams, and industry experts, along with document analysis of company reports and export data. The findings reveal that PT Freeport Indonesia has strong internal capabilities, such as large production capacity and operational experience, which provide a solid foundation for market expansion. However, weaknesses such as high logistics costs and limited knowledge of new markets need to be addressed. Externally, there are significant opportunities driven by global demand and the trend towards sustainability, favoring the use of environmentally friendly materials like copper slag. However, challenges such as market fluctuations and intense competition must be carefully managed. The study recommends strategies for market expansion, including investing in foreign market research, reducing logistics costs through partnerships, and emphasizing the environmental benefits of copper slag. By leveraging its strengths and external opportunities while addressing weaknesses and managing threats, PT Freeport can enhance its competitiveness in the global market. This research highlights the company’s potential for success in expanding its copper slag export market through strategic actions.